Contemporary division of Diyar in the balance of Islamic jurisprudence - Muhammad Gabr Sid Abdellah Gameel (Social Empowerment Journal, 2021)
The study aimed at evaluating the viewpoint and evidence of the Grand Mufti of Egypt concerning the issue of  segregation of  homes of muslims and non-muslims. The study used the critical-analysis methodology to investigate the targets in question.  To gather the required data,  a review of literature was administered. The study came to the conclusion that the Grand Mufti's view that the Scholars' segregation of homes is debatable  proved to be unauthentic because it breaks the tradition of the Salaf ( Our Righteous Ancestors ) who asserted that the segregation of homes is unquestionable. The Grand Mufti's evidence proved to be unauthentic as well. The study recommended that individual Muslims ought to be aware that the segregation of homes of muslims and non-muslims is not a subject of question and not to be influenced by false beliefs.